Internationaler Rotbarschsurvey auf den ozeanischen Sebastes mentella in der Irminger See unter isländischer, deutscher und russischer Beteiligung - Hammer, Cornelius; Kosswig, K. (1996)
A hydroacoustic survey on the oceanic redfish (oceanic Sebastes mentella) in the Irminger Sea and adjacent waters South and East of Greenland was carried out by Iceland, Germany and Russia. During this, about 250 000 nm2 were covered. The acoustic assessment yielded a stock size of approximately 1.6 x 10(6) tonnes or 2.6 x 10(9) individuals. This however, is considered to be an underestimation of the stock, as a result of partial mixing of the stock with the scattering layer. The oceanic redfish concentrations were densest at 200-300 m depth, mainly within temperatures of 3.5 °C to 5 °C. 61 % of the stock were males at an average length of 36 cm and an average weight of 582 g. Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010